2019
DOI: 10.1016/j.jval.2019.04.980
|View full text |Cite
|
Sign up to set email alerts
|

Pit8 Cost-Effectiveness Analysis of Physical Therapy Against Chiropractic for Patients With Acute Low Back Pain in the Us

Abstract: Objectives: The objectives were to assess the efficacy and safety of methylprednisolone or dexamethasone in treatment of ASCI. Methods: A literature search was conducted on PubMed, EMBASE and Cochrane Library from their establishment date through 02/18/18 for studies evaluating the utility of steroids alone in ASCI. Pooled effect estimates were calculated using the random-effects model. Results: 2,956 articles were screened and 10 articles were included in the meta-analysis: three randomized controlled trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…However, the marginal cost-effectiveness of chiropractic over PT suggests that both treatments were quite similar. Such findings are in line with the earlier studies, which found that the effectiveness and total costs of chiropractic and PT as primary treatments were similar to each other right after treatment and after 6 months follow-up [3,22,32].…”
Section: Discussionsupporting
confidence: 92%
“…However, the marginal cost-effectiveness of chiropractic over PT suggests that both treatments were quite similar. Such findings are in line with the earlier studies, which found that the effectiveness and total costs of chiropractic and PT as primary treatments were similar to each other right after treatment and after 6 months follow-up [3,22,32].…”
Section: Discussionsupporting
confidence: 92%
“…Employee engagement is recognized as an important element of organizational effectiveness (Mann and Harter, 2016; Ruck et al , 2017). The main reason behind this is the fact that engaged employees are more productive, profitable, safer and healthier workers (Khodakarami, 2019a; Shuck and Wollard, 2010). In obtaining such aspects of engagement, practitioners and scholars have examined elements that encourage employee engagement (Saks, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the outcome in the short-term, this article focuses on the effects of the assigned treatment on the sick-leave [18]. A high duration of sick-leave may halt employee engagement and impose economic costs on the organization [19,20]. Correspondingly, this study uses the duration of sick leave before treatment for chiropractic and physiotherapy groups.…”
Section: Sample Of Studymentioning
confidence: 99%